Identifying the groundwater sustainability implications of water policy in high-use situations in the Laurentian Great Lakes Basin. Issue 4 (2nd October 2019) - Weekes, Khafi; Krantzberg, Gail; Vizeu Pinheiro, Maria
Abstract: Although the Laurentian Great Lakes Basin contains the largest global store of fresh water, long-term groundwater storage (GWS) decline has been observed in some aquifers supplying communities that intensely use the resource. We consider a hallmark of effective groundwater use policy to be the regulation of aquifer pumping rates consistent with the physical-environmental determinants of sustainable aquifer yield. In this context, we examine policies, from the binational to municipal governance levels, to identify features that can lead to GWS decline in aquifers supplying these communities. As the physical-environmental characteristics determining sustainable yield span many climates and geological settings within the Basin, our findings highlight the need for policies to adapt to local conditions. We urge devolving more management roles to municipal level institutions which, as the nexus between people and central government, may be better poised to set policies in a participatory manner considering the unique physical-environmental characteristics of the aquifers on which their communities rely.